2007
DOI: 10.1111/j.1469-8137.2007.02046.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite profiling of Douglas‐fir (Pseudotsuga menziesii) field trials reveals strong environmental and weak genetic variation

Abstract: Summary• The primary objective of this study was to assess metabolomics for its capacity to discern biological variation among 10 full-sib families of a Douglas-fir tree breeding population, replicated on two sites.• The differential accumulation of small metabolites in developing xylem was examined through metabolite profiles (139 metabolites common to 181 individual trees) generated by gas chromatography mass spectrometry and a series of statistical analyses that incorporated family, site, and tree growth an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 27 publications
(34 reference statements)
6
33
0
Order By: Relevance
“…There are some previously reported correlation analyses in field studies on metabolite levels that corroborate this statement (Robinson et al, 2007;Degenkolbe et al, 2013). That said, the coefficient values of most of the correlations discussed here range from 20.77 to 20.45 with P values lower than 0.05 or 0.001, which can be considered as highly reliable.…”
Section: Possible Relationship Between Basal Respiration and Yield Pesupporting
confidence: 79%
“…There are some previously reported correlation analyses in field studies on metabolite levels that corroborate this statement (Robinson et al, 2007;Degenkolbe et al, 2013). That said, the coefficient values of most of the correlations discussed here range from 20.77 to 20.45 with P values lower than 0.05 or 0.001, which can be considered as highly reliable.…”
Section: Possible Relationship Between Basal Respiration and Yield Pesupporting
confidence: 79%
“…Long-lasting transgenerational plasticity can, however, not be fully excluded and we therefore refer further to (epi)genetic factors (Verhoeven et al 2016). Although (epi)genetic factors are generally considered less determining than environmental factors (Robinson et al 2007;Frank et al 2009;Matsuda et al 2012), our results demonstrate a clear (epi)-genetic signal of metabolic differentiation along T. urticae's invasion gradient. We acknowledge, however, that we cannot exclude neutral processes, such as, for example, serial bottlenecks -including surfing mutations (Klopfstein et al 2006;Travis et al 2007) as potential (co)sources of the found latitudinal metabolomic patterns.…”
Section: Discussionmentioning
confidence: 68%
“…In the present frame work, DHA and F1 showed a significant accumulation of the raffinose family oligosaccharides (RFOs), mannose-1, 6 phosphate,arabinose, and xylulose as compared to DHC, which might display a protective and adaptive role in DHA and F1 genotypes under environmental stresses. Such a role has been proposed for Pseudosuga menziesii genotypes and environmental stress interaction, resulting in a distinctive accumulation of 19 metabolites that exhibited significant variation, among which raffinose, arabinose, xylose, malic acid, and alanine were positively identified (Robinson et al 2007). These forms of sugar are essentially entangled in the plant stress responses, acting as ROS scavengers, cell wall reinforcements, and osmoprotectants that stabilize cellular membranes and maintain turgor Keunen et al 2013).…”
Section: Discussionmentioning
confidence: 98%